Gebruik van draagbare media-apparatuur en mobiele telefoons tijdens het fietsen. - Goldenbeld, Ch.; Houtenbos, M.; Ehlers, E. (My University, 2010)
Increasingly, Dutch cyclists own portable media players and/or mobile phones which they also often use while cycling. This raises the question of how frequently this is done and whether the use of these appliances while cycling contributes to reduced safety. In the summer of 2009, SWOV commissioned Intomart GfK to carry out a questionnaire study. The report discusses this study of the intensity and the manner of using portable media players and mobile phones and of the possible road safety consequences.
Keywords: Fahrradverkehr; Untersuchung; Erhebung; Bewertung; Verkehrssicherheit; Verkehrsunfall; Individualverkehr; Fahrradnutzung; Mobiltelefon; Media Player; Fahrradfahrer